Conductive composite materials
By using low melting point conductors and compatibilizers to form pastes and combining polymers to prepare conductive composites, the problem of difficult to take into account both conductivity and mechanical properties in the prior art is solved, and efficient conductivity and elastic properties are achieved.
Patent Information
- Application Number
- CN202010806124.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2019-08-13
- Filing Date
- 2020-08-12
- Publication Date
- 2025-02-18
- Estimated Expiration
- 2040-08-12
AI Technical Summary
Existing conductive composite materials are difficult to maintain electrical conductivity and mechanical properties under high particle load levels, and liquid metals are prone to leakage.
Low melting point conductors and compatibilizers are used to form pastes, combined with polymers to prepare conductive composites, ensuring that the conductors are evenly distributed in the material and preventing leakage.
The conductive composite material used under different environmental conditions is realized, with excellent conductivity and elastic properties, avoiding the problem of conductor leakage.
Smart Images

Figure CN112397217B_ABST
Abstract
Description
Technical Field
[0001] The present disclosure relates to electrically conductive composites, and more particularly to electrically conductive polymer composites, and methods and compositions useful for preparing such materials. Background Art
[0002] In a broad sense, a conductive composite is any composite material that has significant electrical or thermal conductivity. Such composites contain a conductive phase dispersed in a polymer resin. The unique properties of such composites make them technically superior or more cost-effective than alternative materials in a variety of applications. Therefore, conductive composites have a wide range of uses in fields such as telecommunications, power generation and distribution, defense, aerospace, medicine, and the like.
[0003] Where conductive composites are used, conductivity is not only important, but is often the dominant characteristic of the composite. The conductivity of a material varies depending on the intended use. For some applications, it is important that the effective sheet resistance of the composite is less than 100 Ohm / sq.
[0004] Conductive composites are often made and / or properties are obtained by combining polymer materials with solid conductive particles. In order to obtain sufficient conductivity, i.e., to achieve permeation, high particle loadings, typically in excess of 45% by volume, are often required. The polymers used at these particle loading levels are typically rigid materials. As a result, these particle loading levels result in conductive films and conductive coatings having properties that make them unsuitable or difficult to use (e.g., elongation at break, tensile strength, and thermal stability). Solutions to this problem using liquid metals are plagued by leakage of the metal from the polymer matrix.
[0005] There is also a need for conductive polymer coatings and films having a wide operating temperature range.
[0006] Therefore, there is a need for composite materials that are electrically conductive, avoid metal leakage from the polymer, and have properties (ie, elongation, tensile strength, and thermal stability) that enable a wide range of uses under different environmental conditions. Summary of the invention
[0007] The present disclosure provides a convenient solution to the above problems. In one aspect, the present disclosure provides a conductive composite material comprising: a polymer; a low melting point conductor, i.e., a conductor selected from metals and metal alloys having a melting point below about 60°C; and a compatibilizer. The low melting point conductor and the compatibilizer are usually in the form of a paste.
[0008] The paste provides (1) electrical conductivity without rigidity and (2) increased viscosity and improved flowability, thereby preventing the low melting point conductor from leaking out of the composite.
[0009] The present disclosure provides composite materials that have electrical conductivity and can be elastic. Achieving these properties simultaneously in a single composite material is difficult and often difficult to achieve using common methods of introducing electrical conductivity.
[0010] Composite materials that are both elastic and conductive are particularly useful in applications where they reduce or eliminate harmful electromagnetic interference.
[0011] In another aspect, the present disclosure provides a conductive composite material comprising: a polymer; a low melting point conductor; a compatibilizer; and an optional thickener.
[0012] The conductive composites of the present disclosure are capable of carrying high metal contents and still exhibit excellent elasticity.
[0013] The conductive composite material can also provide a high level of electrical conductivity using a small amount of a low melting point conductor.
[0014] In another aspect, the conductive composite of the present disclosure is in the form of a laminate.The laminated conductive composite contains successive layers of a conductive composition, typically a paste, comprising a low melting point conductor and a compatibilizer.
[0015] In another aspect, the conductive composite material comprises a conductive network that is stably and uniformly and / or continuously entrapped within a polymer matrix. The network comprises a low melting point conductor and a compatibilizer. In this aspect, the conductor is uniformly or evenly distributed throughout the polymer matrix.
[0016] In another aspect, the present disclosure provides a composition, typically in the form of a paste, comprising a metal or metal alloy having a melting point below about 60° C., and a compatibilizer.
[0017] Another aspect of the present disclosure provides a conductive composite material comprising: an elastomer, a conductor selected from metals and metal alloys having a melting point below about 60°C, and a compatibilizer, wherein the conductive composite material has or exhibits a thermal conductivity of about 5×10 5 S / m, a maximum bulk conductivity, an elongation greater than or equal to 50%, and a tensile strength greater than or equal to 3 MPa.
[0018] Additionally, the present disclosure provides an electrically conductive composite material comprising an elastomer, a conductor selected from metals and metal alloys having a melting point below about 60° C., and a compatibilizer.
[0019] The present disclosure also provides a substrate carrying a layer of an electrically conductive composite material, wherein the electrically conductive composite material comprises a polymer, a conductor selected from metals and metal alloys having a melting point below about 60° C., and a compatibilizer.
[0020] The present disclosure also provides a method of preparing a substrate carrying a layer of an electrically conductive composite material, the method comprising heating the electrically conductive composite material disclosed herein and applying it to the substrate.
[0021] In another aspect, the present disclosure provides a method of shielding an electrical component from electromagnetic radiation or interference, the method comprising providing the conductive composite material of the present disclosure between a source of electromagnetic radiation and the electrical component.
[0022] The conductive composite materials disclosed herein can be rigid or flexible. In certain examples, the conductive composite materials are elastic, ie, elastomers.
[0023] The conductive composite materials of the present disclosure can be prepared by combining a liquid metal (eg, a gallium alloy), typically in the form of a paste, with a polymer or prepolymer and, if necessary, curing the prepolymer or polymer.
[0024] The conductive composite may also be made by a method comprising combining a monomer mixture or polymer composition with a composition comprising a conductor selected from metals and metal alloys having a melting point below about 60° C. and a compatibilizer. The process may also optionally include curing the mixture to form the conductive composite.
[0025] In another aspect, the conductive composite material of the present disclosure can be made by laminating a conductive paste onto the surface of a first cured or partially cured polymer, wherein the conductive paste comprises: (a) a conductor selected from metals and metal alloys having a melting point below about 60° C.; and (b) a compatibilizer.
[0026] In another aspect, the conductive composite material of the present disclosure can be made by spreading a conductive paste onto a non-stick surface, applying an uncured polymer onto the paste, and then curing the polymer. The composite material can then be easily removed from the non-stick surface by peeling the composite material off the non-stick surface. After removal from the non-stick surface, if necessary or desired, additional layers of cured or uncured polymer can be added to the conductive paste and cured if necessary to produce a sandwich or laminate structure.
[0027] In the composite material disclosed herein, the paste has the following functions: providing conductivity without unnecessary rigidity; and increasing the viscosity and fluidity of the conductor, thereby preventing it from leaking when the composite material is manufactured or used.
[0028] The present disclosure also provides a liquid metal paste (typically a paste comprising a gallium alloy and a compatibilizer) that exhibits a loss modulus greater than the storage modulus, ie, a tan delta value greater than 1. BRIEF DESCRIPTION OF THE DRAWINGS
[0029] Figure 1: is a photograph of the paste prepared according to Example 2 spread on a release film. The paste is made of a gallium alloy containing 61.0 wt % of Ga, 25.0 wt % of In, 13.0 wt % of Sn and 1.0 wt % of Zn, polyethylene glycol p-(1,1,3,3-tetramethylbutyl)phenyl ether (Triton TM X100), stainless steel powder (as thickener) and stainless steel wire (as thickener).
[0030] Figure 2 is a photograph of the laminated composite material of Example 2. The conductive composite material is a laminate containing polydimethylsiloxane (Sylgard TM 184) paste layer between layers.
[0031] Figure 3 is a series of photographs showing the effect of compression on a silicone sponge filled with a gallium alloy in the direction of the arrows. DETAILED DESCRIPTION
[0032] As used herein, the term "low melting point conductor" refers to a conductor selected from metals and metal alloys having a melting point below about 60°C and mixtures thereof.
[0033] As used herein, the term "conductive" refers to the ability to conduct electricity or to carry an electric current. The term "conductivity" refers to the level at which a particular material conducts electricity. As used herein, a "conductor" refers to a material that has electrical conductivity (ie, conducts electricity).
[0034] As used herein, "substantially leak-proof" means that less than about 10 volume percent of the conductor leaks from the composite at 50 percent elongation.
[0035] As used herein, "conductive network" refers to an interconnected system capable of transporting electrons (ie, forming an electric current) between different regions of a composite material.
[0036] As used herein, the term "flexible" refers to a material that is not rigid, i.e., the material bends rather than breaks, and more specifically, the material has a Young's modulus (E) of less than about 10 gigapascals (GPa). In certain instances, "flexible" as used herein refers to a Young's modulus of less than about 2 GPa. In other instances, "flexible" as used herein refers to a Young's modulus of less than about 1 GPa.
[0037] The terms "conductive mixture," "paste," and "paste layer" are used interchangeably herein.
[0038] Thus, as used herein, the term "stably and uniformly entrapped within the polymer" means that the conductor and the compatibilizer and any optional thickener are permanently retained within the polymer matrix and do not migrate or leak within the composite when the composite is used. In this context, the composite is a substantially uniform blend or mixture of the polymer, the compatibilizer and any optional thickener. The conductivity of the composite does not decrease over a long period of time.
[0039] Thus, the term "stably and uniformly entrapped between polymer layers" as used herein means that the conductor and the compatibilizer and any optional thickener are permanently retained between the polymer layers as layers in the laminated conductive composite and do not migrate or leak within the composite when the composite is used. The electrical conductivity of the laminated composite does not decrease over a long period of time.
[0040] As described above, the present disclosure provides a solution to problems previously encountered in making conductive composite materials. The conductive composite materials disclosed herein include a polymer, a low melting point conductor, and a compatibilizer. Depending on the desired use, these conductive composite materials can be made flexible or rigid. Importantly, when the composite material is bent or otherwise manipulated, the conductor does not leak from the composite material or substantially does not leak from the composite material.
[0041] The conductive composite material herein can be in the form of a laminate or a material blend. In the laminate, the low melting point conductor and the compatibilizer are a mixture (usually in the form of a paste) that is carried on a polymer layer or between polymer layers. The polymer of each layer can be a single polymer material or a mixture of materials. As used herein, the term "conductive mixture layer" refers to a layer of a laminate comprising a low melting point conductor and a compatibilizer.
[0042] The thickness of each layer of the laminate (i.e., the polymer layer and the conductive laminate layer) can be adjusted if necessary to obtain the desired properties of the final composite material. The laminated composite material herein may include a variety of polymers and multiple conductive layers. For example, the laminate may contain a total of five layers, wherein three polymer layers each sandwich a conductive mixture, i.e., the polymer layers are separated by conductive mixture layers (paste layers) except for the edges of the composite material where the polymer layers are in contact with each other. In an example of a composite material as a three-layer laminate (i.e., the conductive mixture layer is sandwiched between two polymer layers), the total thickness of the laminate may be 5 mm, and the thickness of each polymer layer may be about 1 mm. The thickness of the conductive mixture layer of this composition may be about 3 mm. In another example of a three-layer laminate, the thickness of each polymer layer may be about 2 mm, and the thickness of the conductive mixture layer may be about 1 mm. Where weight reduction is important, the composite material will contain fewer layers while providing the desired level of conductivity, and each layer will be as thin as possible.
[0043] Forming the conductive composite as a laminate in which the conductive composition is a continuous layer allows for the use of small amounts of low melting point conductors and compatibilizers to achieve the desired level of conductivity.
[0044] When used to provide shielding, the conductive composites of the present disclosure fabricated as laminates are preferably used with flat parts and with parts having one axis of curvature (e.g., cylinders.) Although laminates can be used to shield parts with complex surface geometries, they are rarely used in such situations because laminates tend to bend when applied to or wrapped around complex surfaces.
[0045] In other examples, the conductive composite material is a blend or mixture comprising a conductor and a compatibilizer, wherein the conductor and the compatibilizer are substantially uniformly distributed throughout the polymer. Such composite materials can be made by combining a monomer mixture or a polymer composition with a low melting point conductor and a compatibilizer, and optionally curing the polymer or polymerizing the monomer mixture. In such conductive composite materials, the low melting point conductor and the compatibilizer are substantially uniformly dispersed throughout the polymer.
[0046] The conductive composite materials disclosed herein in the form of a blend or mixture include a conductive network that is stably and uniformly and / or continuously entrapped in a polymer. The network includes a low melting point conductor (i.e., a conductor having a melting point below about 60° C.) and a compatibilizer. The compatibilizer is a compound or metal that does not form an alloy with the conductor in the composite material or during its manufacture.
[0047] In addition, without wishing to be bound by theory, in a composite material that is a blend of a low melting point conductor and a polymer (i.e., other than a laminate), it is believed that the metal and the compatibilizer form a conductive network within the pores (free volume) created within the polymer during the curing process. In addition, again without wishing to be bound by theory, it is believed that the pore structure of the polymer can be considered to be open, thereby allowing connections to be formed between different regions of the composite material. The compatibilizer is used in conjunction with the low melting point conductor and any optional thickener to hold the conductor in the pores. The combination of the compatibilizer and the conductor can be considered a paste. As described below, the paste behaves more like a liquid than a solid, making the composite material flexible, e.g., bendable. Using a conductor with a melting point below about 60° C. enables the formation of a paste and the formation of a conductive network.
[0048] The conductive composites of the present disclosure, made as blends of polymers, low melting point conductors, compatibilizers, and optional thickeners, can be used, for example, as conductive seals and coatings for a variety of surfaces and materials.
[0049] The conductive composites of the present disclosure, made as blends of polymers, low melting point conductors, compatibilizers, and optional thickeners, are particularly suitable for use as shields on parts with complex surface geometries. Such composites are able to conform to complex surface shapes without bending.
[0050] In certain examples, the conductive composite material of the present disclosure can be manufactured to include redundant conductive paths. "Redundant conductive path" refers to an electrical path that has electrical connections in a three-dimensional manner. As described elsewhere herein, the conductive composite material of the present disclosure, manufactured as a blend of a polymer, a low melting point conductor, a compatibilizer, and an optional thickener, contains a network of low melting point conductors and compatibilizers that are stably and uniformly and / or continuously entrapped within a polymer matrix. As a result, the conductors are uniformly or uniformly distributed throughout the polymer matrix in a three-dimensional manner, thereby creating redundant conductive paths. Bending or crumpling the blend conductive composite material generally does not result in a loss of conductivity across the bend or wrinkle, because another electrical path will be retained around the compression point created by the bend or wrinkle.
[0051] As described above, the present disclosure provides a conductive composite material, which includes a polymer, a low melting point conductor and a compatibilizer. The low melting point conductor and the compatibilizer are usually in the form of a paste, that is, a viscous mixture of the ingredients.
[0052] The polymer can be a rigid polymer, or the polymer can be an elastomer (elastic polymer). The elastic polymer herein can be a thermosetting elastomer or a thermoplastic elastomer. Generally, the polymer used to make the conductive composite material will be selected to be rigid or elastic according to the end use or the way the composite material is applied to the substrate. For example, when the end use requires flexibility, the polymer will be an elastomer so as to be a conductive composite material. In such cases, the composite material can be referred to as a flexible conductive composite material. Thermoplastic elastomers will be useful for manufacturing modes involving the conductive composite material being shaped or formed into a desired configuration or when it is applied to a substrate.
[0053] Thermoset elastomers that can be used to make the conductive composite materials disclosed in this article include: acrylic resins, polyesters and vinyl esters, phenolic resins, amine-functional resins, polyamides (including nylon), polylactic acid, polystyrene, acrylonitrile butadiene styrene, polybenzimidazole, polycarbonate, polyether sulfone, polyoxymethylene, polyaryletherketone, polyetherimide, polyurethane, polyurea / polyurethane hybrids, polyimide, polythioether, furan resins, their copolymers and their mixtures.
[0054] Thermoset elastomers can also be made from epoxy-functional resins that can be homopolymerized using anionic or cationic catalysts and heat, or copolymerized by a nucleophilic addition reaction with a multifunctional crosslinker, also called a curing agent or hardener.
[0055] In some instances, the conductive composite material will optionally be flexible and will be formed from a thermoplastic polymer (e.g., a thermoplastic elastomer). Thermoplastic elastomers that can be used for the conductive composite materials disclosed herein include, for example, polyamides (including nylon), polylactic acid, polystyrene, acrylonitrile butadiene styrene, polybenzimidazole, polycarbonate, polyether sulfone, polyoxymethylene, polyaryletherketone, polyetherimide, polyethylene, polypropylene, polyphenylene oxide, polyphenylene sulfide, polyvinyl chloride, polyester, polyvinylidene fluoride, silicone (including polysiloxanes and polyfluorosilicone), perfluoropolyether, polybutadiene, polyacrylate, polyurethane, polyurea / polyurethane hybrid, thermoplastic vulcanizate, polytetrafluoroethylene, Polyepoxides, polyimides, cyanate esters, polycyanurates, polythioethers and copolymers and mixtures thereof.
[0056] Under typical processing conditions, the viscosity of suitable thermoplastic elastomers for making the conductive composite materials disclosed herein is about 1000 to about 100,000 cP, about 1000 to about 25,000 cP, or about 25,000 to about 50,000 cP, or about 50,000 to about 75,000 cP, or about 75,000 to about 100,000 cP. In certain examples, under typical processing conditions, the viscosity of suitable thermoplastic elastomers for use herein is about 1000 to about 50,000 cP. As used herein, the term "typical processing conditions" includes temperatures from about room temperature (about 25° C.) to about 200° C., or temperatures from about room temperature to about 100° C. Such thermoplastic elastomers are convenient for making flexible materials.
[0057] The compositions and methods disclosed herein employ low melting point conductors. Suitable low melting point conductors are metals and metal alloys having a melting point below about 60°C. In certain instances, the melting point of the low melting point conductor is below about 50°C, or below about 40°C, or below about 30°C, or below about 25°C, or below about 20°C. In certain instances, the melting point is low enough so that the alloy is liquid when initially combined with the compatibilizer and forms a spreadable paste when thoroughly mixed with the compatibilizer.
[0058] In some examples, the low melting point conductor is an alloy containing at least about 50% by weight gallium, bismuth, mercury, or a combination thereof. Suitable gallium alloys also include indium, tin, bismuth, phosphorus, lead, zinc, cadmium, antimony, or a combination thereof. Indium, tin, bismuth, phosphorus, lead, zinc, cadmium, antimony, or a combination thereof may be included as necessary to change the melting point of the alloy.
[0059] The low melting point conductor may include impurities in small amounts, ie, amounts that do not substantially change the rheological properties of the paste or the conductive and mechanical properties of the final conductive composite.
[0060] In one example, the low melting point conductor used in the conductive composite materials disclosed herein is an alloy comprising indium and 50-97 weight percent gallium.
[0061] In another example, the low melting point conductor used to form the conductive composite material disclosed herein is an alloy comprising about 15-30 wt % indium, about 55-80 wt % gallium, and at least one metal selected from tin and zinc. Suitable gallium alloys are available from Indium Corporation.
[0062] Representative gallium alloys for use in the compositions of the present disclosure include alloys having the following compositions and properties:
[0063]
[0064] The low melting point conductor may be selected to achieve suitable properties of the paste composition for making the composite material. The paste composition is preferably homogeneous and is made using the low melting point conductor and the compatibilizer. The paste is typically anhydrous. Water is not required and is typically avoided when making the paste.
[0065] The compatibilizer used in the conductive composite material herein includes nonionic amphiphilic compounds, ionic amphiphilic compounds, metal nanoparticles or a mixture thereof.
[0066] Preparation of the paste can be accomplished, for example, by mixing the low melting point conductor, the compatibilizer, and any optional ingredients using a planetary centrifugal mixer. The resulting paste can be stored for future use.
[0067] The compatibilizers used herein unexpectedly improve the processability (e.g., flowability, ease of application) of the paste. Without wishing to be bound by theory, it is believed that the mixing of the compatibilizer with the low-melting conductor produces a coating of the compatibilizer on the surface of particles or droplets of the low-melting conductor, thereby reducing the surface energy of the low-melting conductor. Additionally, again without wishing to be bound by theory, it is believed that the compatibilizer forms a monolayer or multilayer on the droplets of the low-melting conductor, reducing or preventing oxidation of the conductor, but it does not produce the kind of shell produced by the use of acids.
[0068] In certain examples, the compatibilizers used herein can also be used to thicken the paste, ie, increase the viscosity of the paste.
[0069] Additionally, if oxidation of the metal surface occurs, a compatibilizer may be added to restore the paste. As used herein, "restore" means that a mixture of compatibilizer and low melting point conductor that has been separated can be returned to the form of a homogeneous paste by introducing additional compatibilizer into the separated mixture and subjecting the mixture to appropriate shear conditions as described below.
[0070] In the example where the paste includes particles of a thickener, as described elsewhere herein, the disclosed compatibilizer is believed to enable penetration into the pores or voids formed between the thickener particles. Without wishing to be bound by theory, it is believed that the compatibilizer aids in penetration by reducing the viscosity of the liquid material in the paste. Penetration into the pores is believed to allow for the use of less low melting point conductor and provide uniformity to the paste.
[0071] In certain examples, the paste for forming the conductive composite material contains a low melting point conductor and a compatibilizer, wherein the weight ratio of the low melting point conductor to the compatibilizer is about 5:1 to 50:1, or about 10:1 to 30:1, or about 15:1 to 25:1, or about 20:1 to 25:1. Thus, the amount of the compatibilizer is about 2 wt % to about 20 wt % as a percentage of the low melting point conductor. A particularly useful amount of the compatibilizer is about 4 wt % to about 10 wt % as a percentage of the low melting point conductor. Phase separation should be avoided. At higher levels of compatibilizer, phase separation may occur, which can be addressed using a thickener of the type disclosed elsewhere herein.
[0072] In some instances, the compatibilizer includes inorganic (e.g., metal) nanoparticles having a size in any linear dimension of less than 100 nm, or less than about 90 nm, or less than about 80 nm, or less than about 70 nm, or less than about 60 nm, or less than about 50 nm, or less than about 40 nm, or less than about 30 nm, or less than about 20 nm. Suitable nanoparticles include metals that are insoluble (i.e., insoluble) in low melting point conductors. Metals suitable for use as nanoparticles are those metals whose solubility of gallium in metals is less than 5 mol % at room temperature. Examples of metals suitable for use as nanoparticle compatibilizers herein include copper, nickel, stainless steel, tin, titanium, tungsten, mixtures thereof, and alloys thereof.
[0073] In some embodiments, the compatibilizer is a nonionic amphiphilic compound or a mixture of nonionic amphiphilic compounds. Suitable nonionic amphiphilic compounds include fatty alcohol alkoxylates (including fatty alcohol ethoxylates), alkylphenol alkoxylates (including alkylphenol ethoxylates), fatty acid alkoxylates (including fatty acid ethoxylates), alkoxylated amines (including ethoxylated amines), fatty acid amides, polyoxyethylene-polyoxypropylene copolymers, fatty acid esters of polyhydroxy compounds, glycerol fatty acid esters, sorbitan fatty acid esters, sucrose fatty acid esters, alkyl polyglucosides, fatty amine oxides, sulfoxides, organic phosphine oxides, and mixtures thereof.
[0074] In some instances, the compatibilizer is an ionic compound. Suitable ionic amphiphilic compounds include anionic compounds and cationic compounds. Representative anionic compounds are alkyl sulfates, alkyl ether sulfates, alkyl sulfonates, alkyl ether sulfonates, alkyl phosphates, and alkyl carboxylates. Representative cationic compounds are quaternary ammonium compounds, monoalkyl ammonium salts, dialkyl ammonium salts, and trialkyl ammonium salts.
[0075] The selection of a specific anionic compound (or mixture thereof) or cationic compound (or mixture thereof) and its amount for forming the conductive paste will be determined by the specific polymer used to make the conductive composite. The type and amount of anionic or cationic compound will be selected to avoid degradation or depolymerization of the polymer.
[0076] In certain instances, the compatibilizer is a surfactant.
[0077] In certain embodiments, the compatibilizer is a nonionic amphiphilic compound or a mixture of such compounds. Particularly useful nonionic amphiphilic compounds are alkylphenol ethoxylates. Representative alkylphenol ethoxylates are octylphenol ethoxylates, such as Triton TM X-100 (polyethylene glycol p-(1,1,3,3-tetramethylbutyl)phenyl ether having an average of 9.5 oxyethylene units), and nonyl ethoxylate.
[0078] Other particularly useful nonionic amphiphilic compounds are poloxamers, which are triblock copolymers of poly(ethylene oxide)-poly(propylene oxide)-poly(ethylene oxide) (PEO-PPO-PEO).
[0079] In certain examples, the conductive composite also includes an optional thickener. When used, the thickener is typically combined with the low melting point conductor and the compatibilizer and is thus a component of the paste or conductive mixture layer.
[0080] The thickener used herein is used as a viscosity modifier and can help resist or minimize the flow of low melting point conductors within the paste. The thickener used herein can be an inorganic or organic material. The thickener will not dissolve the conductor or otherwise form a solution with the conductor; they remain solid when mixed with the conductor, but are wetted by the conductor. The thickener is usually used as a particle, such as a rod, a wire, a substantially spherical particle, or a mixture thereof, and the particle size determines the difficulty of the powder and the conductor to form a paste uniformly. Generally, thickeners with higher surface areas are better thickeners than agents with lower surface areas. The combination of thickeners and conductors (such as gallium alloys) is selected to achieve proper wetting of the thickener and the rheology or modulus of the paste. The particle size and amount are selected to produce a paste composition having a tan δ value greater than 1, that is, the paste behaves more like a liquid than a solid, so that the resulting composite material has flexibility.
[0081] In certain examples, the thickener includes particles (eg, rods or wires) of an inorganic thickener having an aspect ratio greater than 2 (ie, the length is at least twice the width). The aspect ratio can be measured using a microscope.
[0082] In some instances, the thickener comprises substantially spherical particles of an inorganic thickener having an average particle size of about 0.1-500 μm (100-500,000 nm). Particles in this size range have sufficient surface area to be used as a thickener to form a paste with a conductor. In some instances, the thickener comprises substantially spherical particles of an inorganic thickener having an average particle size of about 1-25 μm, or about 25-50 μm, or about 50-75 μm, or about 75-100 μm, or about 100-150 μm, or about 150-200 μm, or about 200-250 μm, or about 250-300 μm, or about 300-350 μm, or about 350-400 μm, or about 450-500 μm. In other examples, the thickener includes substantially spherical particles of an inorganic thickener having an average particle size of about 50-150 μm. In other examples, the particles of the inorganic thickener have an average particle size of about 0.1-5 μm.
[0083] In one example, the thickener is an inorganic thickener having an aspect ratio greater than 2 and comprising a rod or wire having a length of about 0.01-10 mm. In some examples, the length of the rod of the inorganic thickener is about 0.01-0.5 mm, or about 0.05-10 mm, or about 0.01-10 mm, or about 0.01-10 mm, or about 0.01-0.1 mm, or about 0.1-1 mm, or about 0.1-1 mm, or about 1-5 mm, or about 5-10 mm. Compared with roughly spherical particles, the use of rods or wires contributes to the conductivity of the final composite material to a greater extent. As a result, the amount of paste required to achieve a certain degree of conductivity can be reduced. The reduction in the amount of paste used to make the composite material can be achieved by reducing the amount of conductor or the amount of thickener.
[0084] In certain examples, the inorganic thickener includes a mixture of rods or strings and substantially spherical particles, or a mixture of rods, strings, and substantially spherical particles.
[0085] In some instances, the thickener includes particles of an organic thickener having an average particle size of about 0.1-500 μm. In some instances, the thickener includes particles of an organic thickener having an average particle size of about 1-25 μm, or about 25-50 μm, or about 50-75 μm, or about 75-100 μm, or about 100-150 μm, or about 150-200 μm, or about 200-250 μm, or about 250-300 μm, or about 300-350 μm, or about 350-400 μm, or about 450-500 μm. In other instances, the thickener includes particles of an organic thickener having an average particle size of about 50-150 μm. In some instances, the average particle size of the particles of the organic thickener is about 0.1-5 μm.
[0086] In the example where the paste further comprises a thickener, the thickener may be used in an amount to produce an appropriate viscosity and / or adjust the conductivity of the paste and the resulting composite material. A suitable concentration of the inorganic thickener in the paste is about 0.1% to 20% by weight of the paste composition. A suitable concentration of the organic thickener in the paste is about 0.1% to 40% by weight of the paste composition.
[0087] The suitable volume amount of thickener in the paste composition is about 5 volume % to 50 volume % of the paste. In certain examples, the amount of thickener is about 5 volume % to about 10 volume %, or about 5 volume % to about 15 volume %, or about 10 volume % to about 20 volume %, or about 15 volume % to about 25 volume %, or about 20 volume % to about 30 volume %, or about 25 volume % to about 35 volume %, or about 30 volume % to about 45 volume %. These amounts facilitate the production of a paste composition having a tan δ value greater than 1, that is, the paste behaves more like a liquid than a solid, thereby making the resulting composite material flexible.
[0088] As described above, the amount of thickener can be reduced when using a rod or wire as a thickener. A suitable amount of a rod or wire thickener in a paste is about 2% to 40% by volume of the paste. In certain instances, the amount of the thickener is about 2% to about 5% by volume of the paste composition, or about 5% to about 10% by volume, or about 10% to about 15% by volume, or about 15% to about 20% by volume, or about 20% to about 25% by volume, or about 25% to about 30% by volume, or about 30% to about 40% by volume.
[0089] Suitable electrical conductivity can be achieved in the conductive composites disclosed herein without using a large amount of solid conductive particles in the paste (i.e., a loading of such particles greater than about 45% by volume). However, in certain instances, if insufficient metal is present in the liquid phase to form the desired level of electrical connection between the metal particles, a loading of metal particles greater than 45% by volume may be used. Thus, particle loading levels higher than 45% by volume (e.g., from about 45% by volume to about 80% by volume) may be used in the paste if necessary.
[0090] In some instances, the thickener for making the conductive composite material is an organic thickener. Suitable organic thickeners include compounds having a melting point higher than 60°C (i.e., a temperature that prevents the thickener from melting together with the alloy (i.e., before or during the manufacture of the composite material)). Examples of such compounds are maltol, phenol, naphthalene, 1-naphthol, 2-naphthol, 4-pyridone and carbon (e.g., including graphite and carbon black). When the organic thickener is a compound with a phenolic hydroxyl group, the compound can react with diisocyanate or polyisocyanate by a hydroxyl group, but the reaction will react slower than carbamate or urea formation. When used appropriately, such compounds can be used to change the properties of the resulting polymer. Alternatively, the organic thickener can be graphite or carbon particles.
[0091] In some instances, the thickener is an inorganic thickener or a combination of inorganic thickeners. Suitable inorganic thickeners include metal oxides (e.g., titanium dioxide and zinc oxide), metals with a melting point above 60°C, or ceramic materials. The metal is selected to have a melting point above 60°C to prevent the thickener from melting before or during the manufacture of the composite material. Suitable metals include nickel, metal oxides of nickel, titanium, tungsten, stainless steel, copper, tin, zinc, ceramics, or a combination thereof.
[0092] The conductive composite material disclosed herein includes about 0.1 volume % to about 50 volume % conductor. The amount of conductor will depend on the intended use of the composite material and the type and amount of other conductors in the composite material. Generally, in the absence of other conductors, higher conductivity will require a larger percentage of conductor. Obviously, when the conductor has a relatively high conductivity, a lower volume of conductor can be used. In some examples, the conductive composite material includes about 0.1 volume % to about 30 volume %, or about 0.1 volume % to about 20 volume %, or about 0.1 volume % to about 10 volume % conductor. In other examples, the conductive composite material includes about 0.5 volume % to about 30 volume %, or about 0.5 volume % to about 20 volume %, or about 0.5 volume % to about 10 volume % conductor. In other examples, the conductive composite material includes about 1 volume % to about 30 volume %, or about 1 volume % to about 20 volume %, or about 1 volume % to about 10 volume % conductor. In other examples, the conductive composite material includes about 5 volume % to about 30 volume %, or about 5 volume % to about 20 volume %, or about 5 volume % to about 10 volume % of the conductor. In certain examples, the amount of conductor is about 2 volume % to about 10 volume %, or about 1 volume % to about 5 volume %, or about 2 volume % to about 5 volume %, or about 5 volume % to about 15 volume %, or about 10 volume % to about 20 volume %, or about 15 volume % to about 25 volume %, or about 20 volume % to about 30 volume %, or about 25 volume % to about 35 volume %, or about 30 volume % to about 45 volume % of the composite material.
[0093] The thickener may be a mixture of at least one organic thickener and at least one inorganic thickener. Mixtures of organic and inorganic thickeners may be used to modify the rheology and modulus of the paste.
[0094] In certain examples, the thickener comprises rods, wires, substantially spherical particles, or mixtures thereof, and the rods, wires, and substantially spherical particles comprise a metal selected from the group consisting of nickel, titanium, tungsten, stainless steel, copper, tin, metal oxides of nickel, zinc, ceramics, and combinations thereof, wherein the substantially spherical particles have an average particle size of about 0.1-500 μm (100-500,000 nm) and the rods and wires have a length of 0.01-10 mm.
[0095] The present disclosure provides a paste composition, which includes a metal or metal alloy (e.g., a low melting point conductor) having a melting point below 60° C. and a compatibilizer, and optionally one or more thickeners. In other examples, the paste composition includes a metal or metal alloy having a melting point below 60° C., a compatibilizer, and at least one thickener selected from an organic thickener and an inorganic thickener.
[0096] In certain examples, the paste composition disclosed herein that can be used to prepare a conductive composite material may have a loss modulus (G") greater than the storage modulus (G'), that is, the tan δ value of the paste composition is greater than 1. Therefore, the paste composition of the present disclosure behaves more like a liquid than a solid. When measured with a dynamic shear rheometer according to ASTM D7175, the viscosity of the paste composition of the present disclosure at 1 Hz is 500-100,000 Pa.s.
[0097] The conductive composite material disclosed herein can be prepared by combining the following (i) and (ii):
[0098] (i) a paste comprising a low melting point conductor and a compatibilizer and optionally a thickener;
[0099] (ii) A mixture of monomers used to form the intermediate composition.
[0100] After combining these materials, the resulting intermediate composition can be cured to form a composite material. Depending on the choice of starting materials, the composite material will be rigid or flexible. It can also be thermoplastic, i.e., flexible when heated.
[0101] Alternatively, the conductive composite material disclosed herein can be prepared by combining (i) and (ii) below:
[0102] (i) a paste comprising a low melting point conductor and a compatibilizer and optionally a thickener;
[0103] (ii) A polymer or a mixture of polymers.
[0104] If necessary, after combining these materials, the polymer can be cured to form a composite material. Depending on the choice of starting materials, the composite material will be rigid or flexible. It can also be thermoplastic, i.e., flexible when heated.
[0105] The laminated composite material of the present disclosure can be made by laminating a conductive paste onto the surface of a first polymer, wherein the conductive paste comprises: (a) a conductor selected from metals and metal alloys having a melting point below about 60° C.; and (b) a compatibilizer, optionally applying a layer of a second polymer onto the conductive paste. The second polymer may be the same as or different from the first polymer. Adding the layer of the second polymer will encapsulate the conductive paste.
[0106] The laminated conductive composite material of the present disclosure can also be made by spreading a conductive paste on a non-sticky surface, applying an uncured polymer on the paste, and then curing the polymer. The composite material can then be conveniently removed from the non-sticky surface by peeling the composite material from the non-sticky surface. If necessary, a second polymer (which can be the same or different from the first polymer) can be optionally applied to the conductive paste. The added layer of the second polymer will encapsulate the conductive paste.
[0107] The non-stick surface may be any suitable non-stick material. Examples of suitable non-stick materials include polytetrafluoroethylene, anodized aluminum, ceramic, and enameled cast iron.
[0108] The conductive composite materials disclosed herein may also include other materials to impart other properties to the composite materials. For example, before forming the composite material, a thermal oxidation stabilizer (a material or additive that improves thermal oxidation stability) may be included in the polyol, diisocyanate or polyisocyanate, or paste composition. Depending on the desired properties of the composite material and the environment in which the composite material is deployed, the thermal oxidation stabilizer may be a phosphate, iron oxide, a phenolic antioxidant, a metal passivator, or a combination thereof. Adding a thermal oxidation stabilizer to the conductive composite materials disclosed herein expands the operating temperature range of the composite material.
[0109] Suitable metal passivators include nitrates (eg, nitric acid), citrates (eg, citric acid), tungstates, molybdates, chromates, and mixtures thereof.
[0110] The sheet resistivity of a particular conductive composite will depend on the end use application. For example, when the composite is to be used to shield electrical components from electromagnetic radiation (e.g., to minimize electromagnetic interference that could damage or harm sensitive electronic equipment), a minimum sheet resistivity of less than 100 Ohm / sq is preferred.
[0111] In certain examples, the conductive composite materials disclosed herein exhibit a conductivity of about 5×10 5 Maximum volume resistivity in S / m.
[0112] In certain examples, the conductive composites disclosed herein exhibit an elongation of greater than or equal to 50%.
[0113] In certain examples, the conductive composites disclosed herein exhibit a tensile strength greater than or equal to 3 MPa.
[0114] In certain examples, the conductive composite materials disclosed herein exhibit a conductivity of about 5×10 5 S / m, a maximum volume resistivity of greater than or equal to 50%, and a tensile strength of greater than or equal to 3 MPa.
[0115] In certain examples, the conductive composite material disclosed herein includes:
[0116] Elastomers;
[0117] Low melting point conductors; and
[0118] Compatibility agent,
[0119] The conductive composite material has or exhibits a conductivity of about 5×10 5 S / m, a maximum volume resistivity of greater than or equal to 50%, and a tensile strength of greater than or equal to 3 MPa.
[0120] Sheet resistivity is a standard measurement and can be determined using a four-point probe.
[0121] In some instances, the conductive composite material is flexible and has an elongation greater than about 50%. In other instances, the conductive composite material is flexible and has an elongation greater than about 10%, or greater than about 20%, or greater than about 30%, or greater than about 40%. The flexible conductive composite material of the present disclosure preferably includes a thermoplastic elastomer. In one example, the thermoplastic elastomer is a thermoplastic polyurethane.
[0122] In some examples, the elongation of the conductive composite material is greater than about 50%. In other examples, the elongation of the conductive composite material is greater than about 10%, or greater than about 20%, or greater than about 30%, or greater than about 40%.
[0123] In some instances, the conductive composite material is flexible and has a tensile strength greater than or equal to 3 MPa. In some instances, the conductive composite material is flexible. In some instances, the conductive composite material has a tensile strength greater than or equal to 3 MPa.
[0124] In some instances, the density of the conductive composite is about 2 to 10 g / mL. In other instances, the density of the conductive composite is about 10 to 20 g / mL. In other instances, the density of the conductive composite is about 1 to 5 g / mL, or about 3 to 8 g / mL. In one example, the density of the conductive composite is less than 7 g / mL. This parameter can be easily measured by determining the mass of a known volume or measuring the volume of water displaced by a known mass.
[0125] The present disclosure also provides products, articles and structures including a substrate carrying a layer of a conductive composite material disclosed herein (in some instances, a flexible conductive composite material disclosed herein). Such products, articles and structures can be made by heating a thermoplastic or thermosetting conductive composite material disclosed herein and applying it to a substrate.
[0126] The conductive composite material disclosed herein can be manufactured as follows:
[0127] The low melting point conductor is combined with a compatibilizer, and the resulting mixture is thoroughly mixed to form a uniform paste, thereby preparing a paste composition. Mixing can be performed by a shear mixer at about 25-2500rpm. In some instances, the shear mixing for forming the paste composition is performed at about 25-125rpm, or about 125-250rpm, or about 250-400rpm, or about 400-700rpm, or about 700-1500rpm, or about 1500-2500rpm. Alternatively, mixing can be performed using a planetary centrifugal mixer. The resulting paste can be stored for future use.
[0128] In certain examples, the conductive composite material of the present disclosure can be prepared by laminating a conductive paste onto the surface of a first polymer, wherein the conductive paste includes: (a) a conductor selected from metals and metal alloys having a melting point below about 60° C.; and (b) a compatibilizer. The second polymer can be the same as or different from the first polymer.
[0129] Example
[0130] Sources
[0131] LBH-P2000 was obtained from Cray Valley and used as received. NH 1220 was purchased from Covestro and used directly. Ga alloy (Indalloy 46L) was purchased from Indium Corporation and used directly. Maltol, titanium powder (size about 100 mesh), 4,4'-methylenebis(cyclohexyl isocyanate), a mixture of isomers (HMDI), and dibutyltin dilaurate (DBTDL) were purchased from Sigma Aldrich and used directly. Stainless steel wire (3 mm × 2 μm) was purchased from Intramicron and used directly. Polydimethylsiloxane (Sylgard TM 184) was obtained from Dow Corning and used as received. Stainless steel powder (Type 316, 325 mesh (44 μm)) was purchased from Atlantic Equipment Engineers and washed with acetone before use.
[0132] The volume percentage of the low melting point conductor gallium was determined by back-calculating the gallium alloy fraction in the composite material after sample fabrication.
[0133] Example A: Preparation of polyurethane prepolymer (Part A)
[0134] The hydroxyl-terminated polybutadiene ( LBH-P2000,M n=2100 g / mol, 50.00 g, 23.8 mmol) and HMDI (19.65 g, 74.89 mmol) were placed in a nitrogen inlet equipped with an overhead stirrer ( The flask was placed in a round bottom flask with a 100°C oil bath and stirred at 175 rpm for 10 minutes. DBTDL (500 ppm) catalyst was then added to the solution using a micropipette and the reaction was allowed to proceed for 2 hours to form a prepolymer (Part A). The neat Part A (without solvent) was poured into a glass jar and stored for future use.
[0135] Comparative Example C-1:
[0136] Preparation of paste:
[0137] 18.51 g of Ga alloy ( 46L) and 3.02g maltol (thickener) were mixed for about 5 minutes.
[0138] Preparation of a composite material (paste) containing 21.8 vol.% Ga alloy:
[0139] Part A (7.64 g) and Ga alloy-maltol paste (21.53 g) were mixed for about 5 minutes using a shear mixer at less than or equal to 100 rpm. NH1220 (2.56 g) was added to the resulting uniform mixture and mixed manually for 1 minute with a spatula. The mixture was then transferred to a Teflon mold and a blade coater was used to cast a film.
[0140] Comparative Example C-2
[0141] Preparation of paste:
[0142] 27.23 g of Ga alloy ( 46L) and 5.86g titanium powder (thickener, about 100 mesh) were mixed for about 5 minutes.
[0143] Preparation of a composite material (paste) containing 27.8 vol.% Ga alloy:
[0144] Part A (8.15 g) and Ga alloy-Ti paste (33.09 g) were mixed using a shear mixer at 100 rpm or less for several minutes. NH1220 (2.56 g) was added to the resulting homogeneous mixture and mixed manually with a spatula for 1 minute. The mixture was then transferred to a polytetrafluoroethylene (PTFE) mold (e.g., manufactured under the trade name PTFE). PTFE) and cast the film using a doctor blade coater.
[0145] Comparative Example C-3
[0146] Preparation of paste:
[0147] 29 g of Ga alloy ( 46L) and 5.17g titanium powder (thickener, about 100 mesh) were mixed for about 5 minutes. Then stainless steel wire (0.52g, 3mm×2μm) was added to the paste and mixed under the same conditions.
[0148] Preparation of a composite material (paste) containing 29.1 vol. % Ga alloy:
[0149] Part A (8.13 g) and Ga alloy-based paste (34.69 g) were mixed using a shear mixer at 100 rpm or less for several minutes. NH1220 (2.73 g) was added to the resulting homogeneous mixture and mixed manually with a spatula for 1 minute. The mixture was then transferred to a container with a trademark A thin (ie, 1-2 mm thick) film was cast in a mold using a doctor blade coater.
[0150] Comparative Example C-4
[0151] Silicone sponge with Ga alloy
[0152] Prepare silicone sponge:
[0153] Silica gel sponge was prepared essentially according to the procedure described by Liang et al. in J. Mater. Chem. C, 2017, 5(7), 1586-1590 as follows:
[0154] 20 g of Sylgard TM Part A and 2g of Part B were mixed for 30 seconds and then immersed in 4 sugar cubes. The mixture of sugar cubes and polydimethylsiloxane (PDMS) was then placed in a desiccator and degassed under vacuum for about 2 hours. The mixture of sugar cubes and PDMS was then cured at 65°C for 3 hours. Afterwards, the PDMS on the surface was wiped off to expose the sugar. The sugar was dissolved in water at 60°C under stirring. The PDMS sponge was obtained by drying at 100°C for 2 hours.
[0155] Preparation of a sponge containing about 53 vol% Ga alloy:
[0156] A piece of silicone sponge was cut in half and then immersed in 15 g of Ga alloy. The container was then placed in a desiccator. A vacuum was used to fill the Ga alloy liquid metal into the PDMS sponge for about 60 minutes.
[0157] Figure 3 The effect of compaction on a sponge filled with a Ga alloy is shown. Figure 3As shown in Figure 1, upon compaction, the Ga alloy leaked out of the silica sponge as droplets of liquid metal; after compaction, only about 23% by volume of the Ga alloy remained in the silica sponge. This can be determined by weighing the sponge before and after compaction.
[0158] Comparative Example C-5:
[0159] Nusil TM LSR-5860 Liquid Silicone Rubber Comparison
[0160] Prepare membrane:
[0161] use 10 g Nusil TM LSR-5860 Liquid Silicone Rubber Part A and 10g Nusil TM LSR-5860 liquid silicone rubber part B was mixed for 1 minute. 10 g of tetrahydrofuran (THF) was added to the mixture and mixed manually with a spatula for several minutes until the mixture was fully dissolved in THF, and then The mixture was mixed again at 2300 rpm for 1 minute. The resulting homogeneous mixture was poured onto a release film and cast with a glass rod. After most of the THF solvent evaporated (about 18 hours / overnight), the film was cured by heating at 100°C for 2 hours.
[0162] Comparative Example C-6:
[0163] Sylgard TM Comparison
[0164] Prepare membrane:
[0165] 10 g Sylgard TM Part 184A and 1g Sylgard TM Mix part 184B for 1 minute. Pour the mixture onto a release film and cast with a glass rod. Heat cure the film at 100°C for 45 minutes.
[0166] Example 1
[0167] Preparation of paste:
[0168] 60.13 g of Ga alloy ( 46L) and 3gTriton TMX100 was mixed for 1 minute. 6.63 g of stainless steel powder (thickener, 325 mesh (44 μm)) was added to the paste and mixed under the same conditions.
[0169] Preparation of a laminate composite material (paste) containing 15.5 vol.% Ga alloy:
[0170] The Nusil 5860 film was prepared using the film preparation procedure described in Comparative Example C-5. After the film was cured, 1 g of the Ga-based paste prepared above in this example was evenly spread on a 1.5"×1.5" cured film. After preparing the film of Comparative Example C-5, 5 g of a mixture of Nusil 5860 Part A and Part B was dissolved in 5 g of THF. The resulting polymer solution was cast on the Ga-based paste and, after most of the THF solvent evaporated (approximately 18 hours / overnight), heated and cured at 100°C for 2 hours. The resulting product was a 1.5"×1.5" laminated film composite.
[0171] Embodiment 2:
[0172] Preparation of paste:
[0173] 75.21 g of Ga alloy ( 46L) and 3.21g Triton TM X100 for 1 minute. 5.45 g of stainless steel powder (thickener, 325 mesh (44 μm)) was added to the paste and mixed under the same conditions. Finally, 4.73 g of stainless steel wire (3 mm × 2 μm, thickener) was added to the paste and manually stirred with a spatula for 1 minute, and then Mix in mixer at 2300 rpm for 1 minute.
[0174] Preparation of a composite material (paste) containing 7.7 vol.% Ga alloy:
[0175] Sylgard was prepared using the membrane preparation procedure described in Comparative Example C-6. TM After the film was cured, 1.82 g of the Ga-based paste prepared in this example was evenly spread on the 1.5" x 1.5" cured film. TM 3g of the mixture of Part A and Part B was cast on the Ga-based paste to completely encapsulate the laminate composite, and cured by heating at 100°C for 45 minutes. The resulting product was a 1.5" x 1.5" laminate film composite.
[0176] Embodiment 3:
[0177] Preparation of paste:
[0178] 25.83 g of Ga alloy ( 46L) and 1.07g Triton TM Mix at X100 for 1 minute.
[0179] Preparation of a laminate composite material (paste) containing 14.1 vol. % Ga alloy:
[0180] The Nusil 5860 film was prepared using the film preparation procedure described in Comparative Example C-5. After the film was cured, 0.59 g of the Ga-based paste prepared above in this example was evenly spread on a 1.5"×1.5" cured film. After preparing the film of Comparative Example C-5, 5 g of a mixture of Nusil 5860 Part A and Part B was dissolved in 5 g of THF. The resulting polymer solution was cast on the Ga-based paste and heated and cured at 100°C for 2 hours until most of the THF solvent evaporated (about 18 hours / overnight). The resulting product was a 1.5"×1.5 laminated film composite.
[0181] Example 4
[0182] Heat Aging:
[0183] The film of Comparative Example C-5 and the laminated films prepared in Examples 1-3 were placed in an oven at 100° C. for 10 days, and their conductive properties and / or elongation were evaluated.
[0184] After curing, the composite materials described in Comparative Examples C-1, C-2, and C-3 could be easily handled and cut into dog-bones for mechanical testing.
[0185] The tensile properties (elongation and instant failure stress) of the thermoplastic polyurethane control and the composites containing the Ga-based paste are summarized in Table 1 below. Apparatus suitable for measuring these properties is commercially available from Instron, Norwood, MA, USA.
[0186] These composites demonstrate the sensitivity of the elastomeric composition to the gallium alloy loading level and show that the methods and compositions disclosed herein result in composites that exhibit excellent elasticity as well as high metal content.
[0187] Table 1
[0188] Mechanical properties of Ga alloy matrix composites
[0189]
[0190] *Indicates samples were aged at 100°C in air for 10 days and tested before and after aging.
[0191] Table 1 shows that the film of Comparative Example C-5 has no degradation in mechanical properties after film aging.
[0192] Table 2 summarizes the conductivity values, measured as attenuation, in dB / mm, for the composites prepared according to Comparative Example C-1, Comparative Example C-2, Comparative Example C-3, Example 1, Example 2, and Example 3. All reported attenuation results were normalized to remove sample thickness as a variable.
[0193] Attenuation was determined using a full 2-port measurement of an X-band waveguide covering 8-12 GHz. The composite sample was pressed between two X-band waveguides, which were connected to a Keysight N5245A network analyzer via a waveguide to coaxial cable converter. A full 2-port calibration was performed using an empty waveguide as a standard. Measurements of the empty waveguide were collected to eliminate waveguide losses in post-processing. Some samples were initially measured using the same center cut as the waveguide opening to ensure proper electrical sealing and determine the amount of loss due to RF leakage, and then a second measurement was performed using a full square sample. Other samples were measured as is.
[0194] When changing from organic to inorganic thickeners, attenuation improves. The combination of inorganic particles and anisotropic metal wires gives the highest conductivity (-16 dB / mm) for non-laminated composites.
[0195] Example 2, a laminate containing both a stainless steel powder thickener and a micron-wire additive other than a compatibilizer, produced an attenuation of -29 dB / mm using only about 7.7 volume % of the gallium alloy. This demonstrates the high conductivity achieved by the disclosed conductive composite using relatively low loading levels of the low melting point conductor.
[0196] The laminated composites of Example 1 and Example 2 were also heat aged in air at 100°C for 10 days and showed no conductivity loss.
[0197] Table 2
[0198] Electrical conductivity of elastic Ga-containing composites
[0199]
[0200] Having described the conductive composite material and methods of making the same in detail, it will be apparent by reference to specific examples thereof that modifications and variations may be made without departing from the scope defined in the appended claims. More specifically, although some aspects of the present disclosure are identified herein as particularly advantageous, it is contemplated that the present disclosure is not necessarily limited to these specific aspects of the present disclosure.
[0201] In addition, the present disclosure includes examples according to the following clauses:
[0202] Item 1. A conductive composite material comprising:
[0203] (a) polymers;
[0204] (b) a conductor selected from metals and metal alloys having a melting point below about 60°C; and
[0205] (c) Compatibilizer.
[0206] Item 2. The conductive composite material of Item 1, wherein the compatibilizer comprises a nonionic amphiphilic compound, an ionic amphiphilic compound, metal nanoparticles, or a mixture thereof.
[0207] Item 3. The conductive composite material of Item 2, wherein the metal nanoparticles are less than 100 nm in any linear dimension and comprise copper, nickel, stainless steel, tin, titanium, tungsten, mixtures thereof, and alloys thereof.
[0208] Item 4. A conductive composite material as described in Item 2 or 3, wherein the nonionic amphiphilic compound is selected from the group consisting of fatty alcohol ethoxylates, alkylphenol ethoxylates, fatty acid ethoxylates, ethoxylated amines, fatty acid amides, polyoxyethylene-polyoxypropylene copolymers, fatty acid esters of polyhydroxy compounds, glycerol fatty acid esters, sorbitan fatty acid esters, sucrose fatty acid esters, alkyl polyglucosides, fatty amine oxides, sulfoxides, organic phosphine oxides and mixtures thereof.
[0209] Item 5. The conductive composite material of any one of Items 2 to 4, wherein the nonionic amphiphilic compound is a surfactant.
[0210] Clause 6. The electrically conductive composite material of any one of Clauses 1 to 5, wherein the polymer is a thermosetting or thermoplastic polymer.
[0211] Item 7. A conductive composite material as described in any one of Items 1 to 5, wherein the polymer comprises polyamide, polylactic acid, polystyrene, acrylonitrile butadiene styrene, polybenzimidazole, polycarbonate, polyether sulfone, polyoxymethylene, polyaryletherketone, polyetherimide, polyethylene, polypropylene, polyphenylene oxide, polyphenylene sulfide, polyvinyl chloride, polyester, polyvinylidene fluoride, silicone, perfluoropolyether, polybutadiene, polyacrylate, polyetherimide, polyurethane, polyurea / polyurethane hybrid, thermoplastic vulcanizate, polytetrafluoroethylene, polyepoxide, polyimide, cyanate ester, polycyanurate, polythioether or a copolymer or mixture thereof.
[0212] Clause 8. The electrically conductive composite material of any of Clauses 1 to 5, wherein the conductor is an alloy comprising at least about 50 weight percent gallium, bismuth, mercury, or a combination thereof.
[0213] Item 9. The conductive composite material of Item 8, wherein the alloy further comprises indium, tin, phosphorus, lead, zinc, cadmium, antimony, or a combination thereof.
[0214] Clause 10. The electrically conductive composite material of any one of Clauses 1 to 9, wherein the conductor is an alloy comprising indium and 50-97 weight percent gallium.
[0215] Clause 11. The electrically conductive composite material of any of Clauses 1 to 10, wherein the conductor is an alloy comprising about 15-30 wt % indium, about 55-80 wt % gallium, and at least one metal selected from tin and zinc.
[0216] Item 12. The conductive composite material of any one of Items 1 to 11, further comprising a thickener.
[0217] Item 13. The conductive composite material of Item 12, wherein the thickener is an organic thickener.
[0218] Item 14. The conductive composite material of Item 12, wherein the thickener is maltol, carbon, phenol, naphthalene, 1-naphthol, 2-naphthol, or 4-pyridone.
[0219] Item 15. The conductive composite material of Item 12, wherein the thickener is an inorganic thickener.
[0220] Clause 16. The conductive composite material of Clause 12, wherein the thickener comprises rods, wires, substantially spherical particles, or mixtures thereof, and comprises a metal selected from the group consisting of nickel, titanium, tungsten, stainless steel, copper, tin, metal oxides of nickel, titanium, tungsten, stainless steel, copper, tin, or zinc, ceramics, and combinations thereof,
[0221] The substantially spherical particles have an average particle size of about 0.1-500 μm, and the rods and wires have a length of 0.01-10 mm.
[0222] Clause 17. The electrically conductive composite material of any one of Clauses 1 to 16, wherein the electrically conductive composite material comprises about 0.1 vol% to 50 vol% conductor.
[0223] Item 18. The electrically conductive composite material of any one of Items 1 to 17, which is a laminate.
[0224] Clause 19. The conductive composite material of Clause 18, wherein the conductor and compatibilizer are substantially uniformly mixed together and form a layer of the laminate.
[0225] Item 20. The conductive composite of any one of Items 1 to 17, wherein the conductor and compatibilizer are substantially uniformly dispersed throughout the polymer.
[0226] Item 21. The conductive composite material of Item 20, wherein the conductor is continuously entrapped in the polymer as a network comprising the conductor and the compatibilizer.
[0227] Clause 22. The conductive composite material of any one of Clauses 1 to 21, wherein the bulk conductivity of the conductive composite material at 20°C is no more than about 5×10 5 S / m, elongation greater than or equal to 50%, and tensile strength greater than or equal to 3 MPa.
[0228] Clause 23. The conductive composite of any one of Clauses 1 to 22, wherein the conductive composite has a density of about 1 to 30 g / cc.
[0229] Clause 24. The electrically conductive composite material of any one of Clauses 1 to 23, wherein the electrically conductive composite material has a density of less than 7 g / cc.
[0230] Item 25. The conductive composite material of any one of Items 1 to 24, further comprising an additive that increases thermo-oxidative stability.
[0231] Item 26. The conductive composite material of Item 25, wherein the additive is a phosphate, iron oxide, a phenolic antioxidant, a metal passivator, or a combination thereof.
[0232] Item 27. A composition comprising: a metal or metal alloy having a melting point below 60°C, and a compatibilizer.
[0233] Clause 28. The composition of Clause 27, wherein the compatibilizer comprises a nonionic amphiphilic compound, an ionic amphiphilic compound, metal nanoparticles, or a mixture thereof.
[0234] Clause 29. The composition according to Clause 27 or 28, wherein the composition further comprises an inorganic thickener or an organic thickener.
[0235] Clause 30. The composition of Clause 29, wherein the inorganic thickener comprises particles of the inorganic thickener that are substantially spherical or have an aspect ratio greater than about 2.
[0236] Clause 31. The composition of Clause 30, wherein the particles of the inorganic thickener are substantially spherical and have a diameter of about 0.1-500 μm.
[0237] Clause 32. The composition of Clause 29, wherein the inorganic thickener comprises particles of the inorganic thickener having an aspect ratio greater than about 2 and a length of about 0.01-10 mm.
[0238] Clause 33. The composition of any one of Clauses 27 to 32, wherein the composition is a paste having a loss modulus (G") greater than a storage modulus (G').
[0239] Item 34. A method of making an electrically conductive composite material comprising combining a mixture of monomers or a polymer composition with (a) a conductor selected from metals and metal alloys having a melting point below about 60°C and (b) a compatibilizer.
[0240] Item 35. The method of Item 34, further comprising curing the mixture of monomers to form the conductive composite material.
[0241] Item 36. A method of making a conductive composite, the method comprising laminating a conductive paste onto a surface of a first polymer, wherein the conductive paste comprises: (a) a conductor selected from metals and metal alloys having a melting point below about 60°C; and (b) a compatibilizer.
[0242] Clause 37. The method of Clause 36, further comprising adding a layer of a second polymer to the surface of the first polymer having the conductive paste.
[0243] Clause 38. The method of Clause 37, wherein the second polymer is the same as or different from the first polymer.
[0244] Clause 39. A conductive composite material comprising:
[0245] Elastomers;
[0246] a conductor selected from metals and metal alloys having a melting point below about 60°C; and
[0247] Compatibility agent,
[0248] The bulk conductivity of the conductive composite material at 20°C is no more than about 5×10 5 S / m, elongation greater than or equal to 50%, and tensile strength greater than or equal to 3 MPa.
[0249] Item 40. A substrate carrying a layer of the electrically conductive composite material of any one of Items 1-26 or 39.
[0250] Clause 41. A method of preparing a substrate carrying a layer of an electrically conductive composite, the method comprising heating the electrically conductive composite of any of clauses 1-26 or 39 and applying the electrically conductive composite to a substrate.
Claims
1. A conductive composite material comprising: (a) polymers; (b) a conductor selected from a metal alloy having a melting point below 60°C; and (c) a compatibilizer, in, The compatibilizer comprises a nonionic amphiphilic compound selected from the group consisting of fatty alcohol ethoxylates, alkylphenol ethoxylates, fatty acid ethoxylates, ethoxylated amines, fatty acid amides, polyoxyethylene-polyoxypropylene copolymers, fatty acid esters of polyhydroxy compounds, alkyl polyglucosides, fatty amine oxides, sulfoxides, organic phosphine oxides, and mixtures thereof, and The conductor is a metal alloy containing at least 50 weight percent of gallium, bismuth, mercury or a combination thereof.
2. The conductive composite material according to claim 1, wherein The compatibilizer also includes ionic amphiphilic compounds, metal nanoparticles or a mixture thereof.
3. The conductive composite material according to claim 2, wherein: The metal nanoparticles have a size of less than 100 nm in any linear dimension and include copper, nickel, stainless steel, tin, titanium, tungsten, mixtures thereof, and alloys thereof.
4. The conductive composite material according to any one of claims 1 to 3, wherein The nonionic amphiphilic compound is a surfactant.
5. The conductive composite material according to any one of claims 1 to 3, wherein The polymers include thermosetting or thermoplastic polymers.
6. The conductive composite material according to any one of claims 1 to 3, wherein The polymer includes polyamide, polylactic acid, polystyrene, acrylonitrile butadiene styrene, polybenzimidazole, polycarbonate, polyether sulfone, polyoxymethylene, polyaryletherketone, polyetherimide, polyethylene, polypropylene, polyphenylene ether, polyphenylene sulfide, polyvinyl chloride, polyester, polyvinylidene fluoride, silicone, perfluoropolyether, polybutadiene, polyacrylate, polyurethane, polyurea / polyurethane hybrid, thermoplastic vulcanizate, polytetrafluoroethylene, polyepoxide, polyimide, cyanate ester, polycyanurate, polythioether or their copolymers or mixtures.
7. The conductive composite material according to claim 1, wherein The metal alloy further includes indium, tin, phosphorus, lead, zinc, cadmium, antimony, or a combination thereof.
8. The conductive composite material according to any one of claims 1 to 3, wherein The conductor is a metal alloy comprising indium and 50-97 weight percent gallium.
9. The conductive composite material according to any one of claims 1 to 3, wherein The conductor is a metal alloy comprising 15-30 wt % indium, 55-80 wt % gallium, and at least one metal selected from tin and zinc.
10. The conductive composite material according to any one of claims 1 to 3, further comprising a thickener.
11. The conductive composite material according to claim 10, wherein The thickener is an organic thickener.
12. The conductive composite material according to claim 10, wherein The thickener is maltol, carbon, phenol, naphthalene, 1-naphthol, 2-naphthol or 4-pyridone.
13. The conductive composite material according to claim 10, wherein The thickener is an inorganic thickener.
14. The conductive composite material according to claim 10, wherein The thickener comprises rods, wires, substantially spherical particles, or mixtures thereof, and comprises a metal selected from the group consisting of nickel, titanium, tungsten, stainless steel, copper, tin, metal oxides of nickel, titanium, tungsten, stainless steel, copper, tin, or zinc, ceramics, and combinations thereof, The substantially spherical particles have an average particle size of 0.1-500 μm, and the rods and wires have a length of 0.01-10 mm.
15. The conductive composite material according to any one of claims 1 to 3, wherein The conductive composite material contains 0.1 volume % to 50 volume % of a conductor.
16. The conductive composite material according to any one of claims 1 to 3, which is a laminate.
17. The conductive composite material according to claim 16, wherein The conductor and compatibilizer are substantially uniformly mixed together and form a layer of the laminate.
18. The conductive composite material according to any one of claims 1 to 3, wherein The conductor and compatibilizer are substantially uniformly dispersed throughout the polymer.
19. The conductive composite material according to claim 18, wherein The conductor is continuously entrapped in the polymer, which acts as a network containing the conductor and the compatibilizer.
20. The conductive composite material according to any one of claims 1 to 3, wherein The bulk conductivity of the conductive composite material at 20°C is no more than 5×10 5 S / m, elongation greater than or equal to 50%, and tensile strength greater than or equal to 3 MPa.
21. The conductive composite material according to any one of claims 1 to 3, wherein The conductive composite has a density of 1 to 30 g / cc.
22. The conductive composite material according to any one of claims 1 to 3, wherein The conductive composite has a density of less than 7 g / cc.
23. The conductive composite material of any one of claims 1 to 3, further comprising an additive to increase thermo-oxidative stability.
24. The conductive composite material according to claim 23, wherein The additive is phosphate, iron oxide, phenolic antioxidant, metal deactivator or a combination thereof.
25. The conductive composite material according to claim 1, wherein The extender includes a nonionic amphiphilic compound selected from the group consisting of glycerol fatty acid esters, sorbitan fatty acid esters, sucrose fatty acid esters, and mixtures thereof.
26. A composition comprising: Metal alloys with a melting point below 60°C, and compatibilizers, wherein the compatibilizer comprises a nonionic amphiphilic compound selected from the group consisting of fatty alcohol ethoxylates, alkylphenol ethoxylates, fatty acid ethoxylates, ethoxylated amines, fatty acid amides, polyoxyethylene-polyoxypropylene copolymers, fatty acid esters of polyhydroxy compounds, alkyl polyglucosides, fatty amine oxides, sulfoxides, organic phosphine oxides, and mixtures thereof, and Wherein, the metal alloy contains at least 50 weight % of gallium, bismuth, mercury or a combination thereof.
27. The composition of claim 26, wherein The compatibilizer also includes ionic amphiphilic compounds, metal nanoparticles or a mixture thereof.
28. The composition of claim 26 or 27, wherein The composition also includes an inorganic thickener or an organic thickener.
29. The composition of claim 28, wherein The inorganic thickener includes particles of the inorganic thickener that are substantially spherical or have an aspect ratio greater than 2.
30. The composition of claim 29, wherein The particles of the inorganic thickener are substantially spherical and have a diameter of 0.1-500 μm.
31. The composition of claim 28, wherein The inorganic thickener includes particles of the inorganic thickener having an aspect ratio greater than 2 and a length of 0.01-10 mm.
32. The composition of claim 26 or 27, wherein The composition is a paste having a loss modulus (G") greater than a storage modulus (G').
33. The composition of claim 26, wherein The extender includes a nonionic amphiphilic compound selected from the group consisting of glycerol fatty acid esters, sorbitan fatty acid esters, sucrose fatty acid esters, and mixtures thereof.
34. A method for preparing an electrically conductive composite material, the method comprising combining a mixture of monomers or a polymer composition with (a) a conductor and (b) a compatibilizer, the conductor being selected from a metal alloy having a melting point below 60°C, in, The compatibilizer comprises a nonionic amphiphilic compound selected from the group consisting of fatty alcohol ethoxylates, alkylphenol ethoxylates, fatty acid ethoxylates, ethoxylated amines, fatty acid amides, polyoxyethylene-polyoxypropylene copolymers, fatty acid esters of polyhydroxy compounds, alkyl polyglucosides, fatty amine oxides, sulfoxides, organic phosphine oxides, and mixtures thereof, and The conductor is a metal alloy containing at least 50 weight percent of gallium, bismuth, mercury or a combination thereof.
35. The method of claim 34, further comprising curing the mixture of monomers to form the conductive composite material.
36. The method of claim 34, wherein: The extender includes a nonionic amphiphilic compound selected from the group consisting of glycerol fatty acid esters, sorbitan fatty acid esters, sucrose fatty acid esters, and mixtures thereof.
37. A method of preparing a conductive composite material, the method comprising laminating a conductive paste onto a surface of a first polymer, wherein: The conductive paste comprises: (a) a conductor; and (b) a compatibilizer, wherein the conductor is selected from a metal alloy having a melting point below 60° C. wherein the compatibilizer comprises a nonionic amphiphilic compound selected from the group consisting of fatty alcohol ethoxylates, alkylphenol ethoxylates, fatty acid ethoxylates, ethoxylated amines, fatty acid amides, polyoxyethylene-polyoxypropylene copolymers, fatty acid esters of polyhydroxy compounds, alkyl polyglucosides, fatty amine oxides, sulfoxides, organic phosphine oxides, and mixtures thereof, and The conductor is a metal alloy containing at least 50 weight percent of gallium, bismuth, mercury or a combination thereof.
38. The method of claim 37, further comprising adding a layer of a second polymer to the surface of the first polymer having the conductive paste.
39. The method of claim 38, wherein: The second polymer is the same as or different from the first polymer.
40. The method of claim 37, wherein: The extender includes a nonionic amphiphilic compound selected from the group consisting of glycerol fatty acid esters, sorbitan fatty acid esters, sucrose fatty acid esters, and mixtures thereof.
41. A conductive composite material comprising: Elastomers; A conductor selected from a metal alloy having a melting point below 60°C; and Compatibility agent, in, The bulk conductivity of the conductive composite material at 20°C is no more than 5×10 5 S / m, elongation greater than or equal to 50%, and tensile strength greater than or equal to 3Mpa, wherein the compatibilizer comprises a nonionic amphiphilic compound selected from the group consisting of fatty alcohol ethoxylates, alkylphenol ethoxylates, fatty acid ethoxylates, ethoxylated amines, fatty acid amides, polyoxyethylene-polyoxypropylene copolymers, fatty acid esters of polyhydroxy compounds, alkyl polyglucosides, fatty amine oxides, sulfoxides, organic phosphine oxides, and mixtures thereof, and The conductor is a metal alloy containing at least 50 weight percent of gallium, bismuth, mercury or a combination thereof.
42. The conductive composite material of claim 41, wherein The extender includes a nonionic amphiphilic compound selected from the group consisting of glycerol fatty acid esters, sorbitan fatty acid esters, sucrose fatty acid esters, and mixtures thereof.
43. A substrate carrying a layer of the electrically conductive composite material of any one of claims 1 to 25 or 41 to 42.
44. A method of preparing a substrate carrying a layer of an electrically conductive composite material, the method comprising heating the electrically conductive composite material of any one of claims 1 to 25 or 41-42 and applying the electrically conductive composite material to a substrate.
Citation Information
Patent Citations
Liquid-state metal electronic paste and preparation method thereof
CN107452436A